Pengaruh Komposisi Material Komposit PAni-TiO2 Yang Disintesis secara Elektrodeposisi Terhadap Laju Korosi Pada Baja Karbon Rendah - Eka Sulistyaningsih; Nidia Lestari (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
The use of carbon steel to meet human needs is increasing every year. Steel is not a rust-resistant material, so it can corrode over time, especially Indonesia is a tropical country that has high rainfall and humidity. Almost all industrial sectors have problems with corrosion. Problems that arise can be in the form of damage, the age of use of goods that do not meet expectations until inadequate safety factors. This study aims to study the effect of low carbon steel coating composition using the PAni-TiO2 composite material. Coating of PAni-TiO2 composite on low carbon steel was carried out by the electrodeposition method on the acid medium and LiCl salt. TiO2 is synthesized by the sol-gel method, while PAni is synthesized by electrochemical polymerization along with electrodeposition. Based on the results of the study of the highest corrosion rate the Plate was produced without inhibitors with a value of 0.007359 mpy, while the lowest corrosion rate was produced by Plate 2 with a value of 0.003666 mpy. The best composition for protecting the Plate from corrosion is 10-3 M PAni and 10-2 M TiO2.